Improving Students English Vocabulary Through Watching Video, and Role Play, An action Research at the Forth Grade Students of SDIT Azzahrah Gowa - Sakinah Islah Hunnufus; Syamsiarna Syamsiarna; Erwin Akib (Institut Agama Islam Negeri Palopo, 2023)
This research aimed to improved the students’ vocabulary through short video and role play technique, this research was conducted in SDIT Azzahrah Gowa. In this research, the researcher collaborate video and role play to improving students’ English vocabulary. The data had been counted by the researcher, then the researcher consider about the improvement of the students. In conducted this research, the researcher gave the students two technique for improving their vocabulary, especially verb and adjective, the technique were through watching video, and playing role play. The data were got using the test for the students, then the data counted by researcher by using quantitative method of data collection technique, and also through documentation with 6 students in the classroom. The Results of this research showed that role play together the videos can improve the students’ vocabulary, especially in verb and adjective vocabulary, it proven by the results of the test, where all of students get significant improvement in every cycle of test.